(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents the design of a film-laying machine equipped with a leveler-compactor for potato ridges, along with the results of its field trials. The proposed machine demonstrated its ability to simultaneously perform the processes of leveling and compacting the ridge, creating furrows, and laying film in a uniform manner. Experimental tests confirmed that the machine’s agrotechnical and operational indicators fully comply with established standards, substantiating the recommendation of this design for use in potato cultivation technology.